Intercultural Communication Accommodation in Interethnic Family - Christina Rochayanti (The Indonesian Journal of Communication Studies, 2010)
Interethnic family is a family consisting of two different ethnics due to the legal unity of couple from different ethnic groups (Sundanese and non-Sundanese). Ethnic differences substitute different cultural background. The focus of this research is the condition in which culture can be accommodated by interethnic family. The aim of this research is to gain the picture of the attitudes of interethnic family in facing their different cultures. Symbolic Interaction Theory and Accommodation Theory are utilized to analyze the accomodated condition of intercultural family. Qualitative method is used in this research; data collecting is conducted through depth interview, involving 13 interethnic families. The families chosen are those which have child and reached 10 years of marriage. The result of the research shows that accommodated condition in interethnic family is the attitude of educating children and of getting aquainted with extended family. Open-mindednes in interethnic family includes the matters of children education, language used, children’s name, activities outside of school, school selection. Yet, for the children’s mate, interethnic families want their children to marry spouse from the same religion, no matter what their ethnics are. Social intercourse, especially with extended family, is considered as family recreation, studying cuisine, and introducing cultural elements to children. The involvement of wife in customary events is to support the husband’s position and to keep the relation to the husband’s extended family.